Transforming learning through semantic e-learning experience - Hazalina Hashim (2012)
Semantic e-learning aspires to transform e-learning experience towards more productive and innovative learning organizations, since these emerging technologies allow defining a meaning (semantics) of learning materials, making it possible to fill the gap between human and machine understanding. The focus of this paper lies on a conceptual level, presenting the needs of semantic web technologies and discussion on fundamental component underlies to model semantic e-learning system namely metadata, ontologies, RDF and OWL. Finally, it highlights the significance of semantic e-learning implementation in transforming learning to another level of learning experience.